Prognostic value of the E/e′ ratio among octogenarians in Singapore. Issue 1 (9th August 2013) - Arasaratnam, Punitha; Lee, Evelyn
Abstract : Background: This study sought to investigate the prognostic value of the medial E (early transmitral flow velocity) to e′ (early diastolic mitral annulus velocity) ratio (E/e′) using the standard cutoff value of 15 among octogenarians stratified according to left ventricular ejection fraction (LVEF), atrial fibrillation (AF) and diabetes. Methods: We examined a consecutive, single-centre cohort of 1197 subjects (male = 39.3%, female = 60.6%) between 80 and 89 years old (mean ± SD = 82.9 ± 2.81) who underwent transthoracic echocardiography from January 2009 to January 2011. E/e′ and LVEF were measured. These subjects were prospectively followed up for 29 months (mean ± SD = 12.8 ± 7.9). Primary endpoint was all-cause mortality. Results: In univariate analysis, patients with underlying AF (AF vs no AF, p<0.001), diabetes (diabetes vs no diabetes, p<0.001), cancer (cancer vs no cancer, p<0.001), LVEF <45% (≥45% vs <45%, p<0.001) or an E/e′ ≥15 (≥15 vs <15, p<0.001) had a poorer prognosis. Gender had no significant effect on prognosis (p<0.08). In multivariate analysis, age, AF, diabetes, cancer, a LVEF <45% and E/e′ ≥15 were significant, independent predictors of a poor prognosis. Conclusions: E/e′ is a predictor of mortality among octogenarians independently of LVEF, AF and diabetes.